2019
DOI: 10.1002/ldr.3408
|View full text |Cite
|
Sign up to set email alerts
|

Solar photovoltaic panels significantly promote vegetation recovery by modifying the soil surface microhabitats in an arid sandy ecosystem

Abstract: The arid sandy areas have great potential for producing solar power, and a large number of solar photovoltaic (PV) power (SPP) stations have been set‐up in these regions across the world. Construction of SPP at large scale certainly changes the land surface with consequences on the local ecosystem. However, few studies have focused on these impacts. This study explored the influence of SPP on vegetation by modifying microhabitats. The soil water content (SWC), evaporation, photosynthetically active radiation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 44 publications
2
42
1
1
Order By: Relevance
“…Early studies also suggest that agrivoltaics installations could also provide other benefits. For example, water usage for some crops and grasses appears to decrease when the crops are located below PV panels, with greater water savings achieved in arid regions (Elnaz Hassanpour Adeh, Selker, and Higgins 2018;Liu et al 2019;Elamri et al 2018;Barron-Gafford et al 2019). One study found that PV panels with crops grown below were on average 8.9 ℃ cooler during daylight hours than panels without crops.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies also suggest that agrivoltaics installations could also provide other benefits. For example, water usage for some crops and grasses appears to decrease when the crops are located below PV panels, with greater water savings achieved in arid regions (Elnaz Hassanpour Adeh, Selker, and Higgins 2018;Liu et al 2019;Elamri et al 2018;Barron-Gafford et al 2019). One study found that PV panels with crops grown below were on average 8.9 ℃ cooler during daylight hours than panels without crops.…”
Section: Introductionmentioning
confidence: 99%
“…However, PV power plants are a mixture of PV arrays, shadows, and different types of soil or vegetation [14]. The mixture inevitably leads to PV power plants having similar spectrums with other objects on a pixel scale over large regions [27,31].…”
Section: The Importance Of Textural Variables In the Rf Model To Map Pv Power Plantsmentioning
confidence: 99%
“…Utility-scale PV power plants caused many potential environmental impacts during the process of construction and operation. The environmental impacts include changes in local microclimate [7][8][9][10][11], changes in albedo [1,12,13], changes in vegetation cover [14,15], land use and land cover change [16,17], and impacts on habitat biodiversity [18,19]. The construction of PV power plants in various landscapes, such as desert, mountain, coast, lake [20][21][22], has also led to the differences in their environmental effects.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both on-site (e.g. Barron-Gafford et al, 2016;Grodsky & Hernandez, 2020;Liu et al, 2019) and satellite (e.g. Zhang & Xu, 2020) observations have shown complex and location-dependent changes to the microclimates and shifts in local ecosystems after the construction of desert solar farms across the world.…”
Section: Introductionmentioning
confidence: 99%